Student voices in academic writing: PsychLiverpool a community for meaning making - Alexandra Forsythe (Association for Learning Development in Higher Education (ALDinHE), 2019)
The practice and expectations of academic communication are changing, and blogging provides a socially liberating mechanism by which to support the development of student writing and literacy. The study reported here examines the impact of an academic–student partnership in supporting the development of student discourse. Anonymous feedback gathered from both the contributors and readers of the student blog, PsychLiverpool was analysed using automated text analysis. The analysis identified that high levels of positive emotion were associated with PsychLiverpool. Students valued its capacity to trigger thinking and insight, and the social and networking relationships the blog offered. PsychLiverpool empowered students to expand their learning networks outside of their classroom and peer network by connecting them with like-minded students and academics.  By providing students with safe opportunities to develop their skills and networks, it fulfilled their needs for affiliation and achievement, power and reward. The particular advantage of PsychLiverpool was that in operating outside of traditional university processes of assessment and feedback, students were more motivated to write about and engage with academic language on their own terms.